[UNQUALIFIED SUPPORT FOR H.R. 673] - HARRIS R (Tufts Archival Research Center, 2007)
Letter from the Virginia State Fireman's Association to Representative Rich Boucher, pledging support for his bill which would implement a panel to identify ways to make cigarettes more fire safe. Claims that the other bills in circulation do not take into consideration the panel's research, and for that reason, they will not support it.